Electrical correlation of double-diffused metaloxidesemiconductor transistors exposed to gamma photons, protons, and hot carriers - Palumbo, Félix Roberto Mario (2011)
Double-diffused metaloxidesemiconductor n-channel power transistor devices were subjected to a high electric-field stress, gamma photons 60Co, and 10-MeV proton radiation, and were comparatively analyzed. The direct-current currentvoltage and high-frequency capacitancevoltage techniques were used to characterize the two different regions under the gate oxide in this kind of devices. The SiSiO2 interfaces at the channel side and at the drain side are characterized after thermal annealing. The correlation of the interface states with the trapped charge is a good quantitative tool to compare the effects from different degradation mechanisms. It is shown that, under given conditions, each kind of stress exhibits its own signature in the interface states versus the oxide charge plot.